Accountability of Budget Users and Proxy Budget users on the Emergence of State Losses in the Procurement of Government Goods/Services - Rustanto (Yuridika, 2022)
Many criminal acts of corruption originate from the procurement of goods/services which turns out to not make the application of the article on corruption crimes to matters relating to state losses or the application of corruption crimes to KPA and PA actions important to get attention, because many parties are certainly familiar with the character of law enforcement for criminal acts of corruption, which are always linked with administrative errors. Based on this background, this research raises the title: "Criminal legal responsibility for budget users and budget users authority in the procurement of government goods/services for the occurrence of state losses.” The purpose of this study is to analyze and find the ratio of the legal liability of PA and KPA in the procurement of government goods/services for the occurrence of state losses and legal consequences for the implementation of PA and KPA duties that cause state losses in the procurement of government goods/services. The research method used is legal research (doctrinal research) and the approach used is the statutory approach, case study, conceptual approach, and comparative approach. The results of this study, namely the Legis Ratio of accountability for PA and KPA for the occurrence of state losses, is because PA and KPA are state officials who have special authority which in fact is not owned by everyone, even public officials, so that, according to the legal principle of deen bevoegdheid zonder verantwoordenlijkheid (there is no authority without accountability), it is logical that, when exercising this authority, when the PA and KPA make a mistake, there are juridical consequences, but the mistakes made by the PA and KPA cannot be generalized immediately. The mistakes made by the PA and KPA must be analyzed, to find out the qualifications for the responsibilities of the PA and KPA, whether administrative, criminal, and/or civil liability. This, when associated with the ten-to-one rule principle, should not allow the PA and KPA to be held accountable for more than the mistakes made.